SELECTION OF SMALL-AMPLITUDE DEFORMATION ANOMALIES – PRECURSOR OF LOCAL TRANSCARPATHIAN EARTHQUAKES WITH TAKING INTO ACCOUNT THE METEOTHERMOELASTIC DEFORMATIONS - Nazarevych, A.; Nazarevych, L.; Bashtevych, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The purpose of the article is to present a methodology of studies and reduction of meteothermoelastic deformations from extensometers data and the results of selection with its application of small amplitude deformation anomalies – precursors of local Transcarpathian earthquakes. The studies of meteothermal influences on the data of geophysical observations regime and the development of ways to taking into account such influences is one of the important tasks in conducting of geodynamic monitoring. This is especially relevant for extensometers studies. The research methodology consist of conducting a correlation analysis of extensometer and meteortemperature data and reduction of selected seasonal meteothermoelastic strains from variational deformations time series. As a result of those researches, in particular, the correlation between the temperature of air and deformations of the rocks massif at the "Muzhievo" observation point (Ukrainian Transcarpathians) was studied. The reduction of selected seasonal meteothermoelastic strains was carried out and a low amplitude deformation anomaly – the precursor of the local Transcarpathian earthquake with a magnitude M=3.3 at an epicenter distance of 31 km is identified. Selected anomaly has an amplitude (in relative deformations) ~3·10-7 (in comparison with the value of the seasonal meteothermoelastic variations ~14·10-7), it is 5-7 times greater than the amplitude of difference fluctuations (0.5·0.7·10-7) between the registered variations of deformations and the "regular" seasonal meteothermoelastic wave. The "precursor" duration of the anomaly is about 5 months. The practical significance of the work consists, in particular, in the fact that the application of the developed technique provides reduction of meteothermal influences and allows the search of low-amplitude deformation anomalies – precursors of earthquakes against the background of thermoelastic deformations. This, in fact, many times increases the actual sensitivity and, respectively, the zone of geodynamic and seismoprognostic control of concrete point of extensometers observations.
Keywords: seismoprognostic studies; deformation of rocks; meteothermal influence; thermoelastric strain; anomaly – precursor of earthquake; Ukrainian Transcarpathians